Structural insights into the twist-bend nematic phase from the integration of 2H-NMR data and modelling: CB7CB and CB6OCB as case studies. Issue 13 (8th December 2018) - Greco, Cristina; Ferrarini, Alberta; Luckhurst, Geoffrey R.; Timimi, Bakir A.; Zimmermann, Herbert
ABSTRACT: The appearance of some special features in 2 H-NMR spectra, which could not be explained by the conventional nematic order, was crucial for the discovery of the twist-bend nematic (NTB ) phase. Such features reflect the order and symmetry of the local environment of a probe and in principle their analysis can provide quantitative insights into the structural parameters of the phase. We have developed a methodology for the analysis of experimental data, different from the approaches that are normally used for two main reasons: (i) the structural features of the NTB phase, specifically its local polarity, biaxiality and chirality, are consistently taken into account; (ii) the molecular features are introduced in a detailed way, through molecular modelling. We have applied this methodology to analyse 2 H-NMR quadrupolar splittings for two representative systems, CB7CB and CB6OCB. The integration of theory, computational modelling and experiment allows us to extract quantitative information from the experimental data and to predict various properties, even not directly probed by measurements. We discuss how the molecular differences between CB7CB and CB6OCB translate into a different phase behaviour and we address issues concerning the distinguishing features of the NTB phase, such as the definition of a local tilted director. Graphical Abstract: